Metallocene Hydrides: Their Didactic Value for Teaching Organometallic Chemistry - Antonio Togni (CHIMIA, 2025)
Metallocene hydrides, Cp2MHn (n=1-3), are complexes known for elements of Groups 3 to 8. Their properties can be understood by the use of a common qualitative MO diagram.